(3TQM CSeGA Gddg GdMSfis - (3YHO GdSdGe Hf YHO GdQMef Hf eMeO GddNej GdETHjdj, CHh GdMce,J (B536 (3g` s ((3Ydi Hf LeYg Hf CHj GdMSf GdgdGdi GdMehi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HGSeg JaJJM GdeWGdH , hjMeOg hMSf GdKfGA Ydjg JNJJe GdeBQH CeG HYO EjgG Gdhdi aEfc SCdJfi Cf CTQM dc eYGfi bQGA QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3YdefG Gddg hEjGc ef Yedg , hCLRd MXfG hMXc ef eYQaJg Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
Keywords: (3GdCOHs